2012
DOI: 10.1007/s00604-012-0777-6
|View full text |Cite
|
Sign up to set email alerts
|

Determination of mercury(II) by surface-enhanced Raman scattering spectroscopy based on thiol-functionalized silver nanoparticles

Abstract: Silver nanoparticles (Ag NPs) modified with sodium 2-mercaptoethanesulfonate (mesna) exhibit strong surface-enhanced Raman scattering (SERS). Their specific and strong interaction with heavy metal ions led to a labelfree assay for Hg(II). The covalent bond formed between mercury and sulfur is stronger than the one between silver and sulfur and thus prevents the adsorption of mesna on the surface of Ag NPs. This results in a decrease of the intensity of SERS in the presence of Hg(II) ions. The Raman peak at 795… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(40 citation statements)
references
References 47 publications
1
39
0
Order By: Relevance
“…18) [105]. Similarly, an SERS determination of Hg 2+ with 2-mercaptoethanesulfonate modified Ag NPs was described by Chen et al [114]. Our group designed a colorimetric and SERS dual-signal sensor for Hg 2+ by facilely mixing Bismuthiol II and Au NPs, without dye tag [115].…”
Section: Reviewsmentioning
confidence: 88%
“…18) [105]. Similarly, an SERS determination of Hg 2+ with 2-mercaptoethanesulfonate modified Ag NPs was described by Chen et al [114]. Our group designed a colorimetric and SERS dual-signal sensor for Hg 2+ by facilely mixing Bismuthiol II and Au NPs, without dye tag [115].…”
Section: Reviewsmentioning
confidence: 88%
“…Chen et al [51] showed that AgNPs modified with sodium 2-mercaptoethanesulfonate (mesna) exhibit strong surface-enhanced Raman scattering (SERS). They used mesna as modifying agent for AgNP surfaces to form complexes of mercury(II) ions binding to reactive adsorption sites on the sorbent surface.…”
Section: Preconcentration Of Mercurymentioning
confidence: 99%
“…2C). Chen et al (2012) demonstrated a label-free assay for Hg 2+ sensing using 2-mercaptoethanesulfonate (MESNA) modified Ag NPs. The covalent bond formed between Hg 2+ and sulfur prevents the adsorption of MESNA on the Ag surface, thus led to the intensity decrease in SERS signals for MESNA (Fig.…”
Section: Reporter Detachmentmentioning
confidence: 99%